2018
DOI: 10.1111/1750-3841.14406
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Processing Condition of Instant Rice to Lower the Glycemic Index

Abstract: White rice is classified as having a low to high glycemic index (GI) depending on its amylose:amylopectin ratio. High GI food can be detrimental to diabetics since they can rapidly increase the glucose level in blood during digestion. Instant rice is increasing in popularity and is produced by dehydrating whole grain cooked rice, therefore, to make it more suitable for diabetics, the effect of the processes involved in the production on GI were tested. The objective was to optimize cooking temperature and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The formation of starch crystals in the cookies would lead to the resistance of the cookies against enzyme hydrolysis hence, an increase in the resistant starch. In their study, Ritudomphol and Luangsakul (2019) , reported an increase in the resistance starch of an instant rice. They attributed this increase to the formation of starch crystal as a result of high processing temperature.…”
Section: Resultsmentioning
confidence: 96%
“…The formation of starch crystals in the cookies would lead to the resistance of the cookies against enzyme hydrolysis hence, an increase in the resistant starch. In their study, Ritudomphol and Luangsakul (2019) , reported an increase in the resistance starch of an instant rice. They attributed this increase to the formation of starch crystal as a result of high processing temperature.…”
Section: Resultsmentioning
confidence: 96%
“…Rice cooked at higher temperature (90 °C) showed lower peak viscosity and breakdown in pasting properties, as compared to that cooked at lower temperature (82 °C). Cooking at 82 °C with 1.9fold water volume was considered optimal to produce lower GI instant rice [47]. Sonia and colleagues (2015) reported that when cooked white rice was cooled for 24 hours at 4 degrees centigrade (°C) and then reheated it showed lower glycemic response as compared to freshly cooked white rice.…”
Section: Resultsmentioning
confidence: 99%
“…The appropriate cooking method as well as the consumption of other foods and nutrients, like fat and protein together with rice in mixed meals, has therefore been suggested as a way to reduce the glycemic index of rice-based meals [12,16]. It has therefore been suggested that the development of instant rice products with lower GI values will be helpful to a wider range of population, particularly for the obese and diabetic people [47]. The data on the GI and GL values of commonly consumed Omani rice dishes as well as of Arsiya and Harees has been reported for the first time and will be very helpful in the daily meal planning for both the normal people and diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the other mathematical algorithms were also developed based on glucose absorption through the intestinal walls and insulin release as follows (153,154) . Equations (30)(31)(32) were devised for people with diabetes, and equation ( 33) represents glucose released based on mass equivalents (154) . The limitations of these models are that these are developed based on human clinical trials and the physical activity and stress levels are not taken into consideration.…”
Section: In Silico Modelsmentioning
confidence: 99%
“…To give a further example, rice normally has a high GI, and since rice is one of the staple foods, an attempt has been made to reduce the GI by adjusting the cooking temperature and water ratio. Rice cooked under the optimised conditions of 82°C with a water to rice ratio of 1.9 had a lower GI when compared with rice cooked at higher temperature and with lower water content, because the latter condition creates more voids and degrades the starch quickly, making it vulnerable to digestive enzymes (32) . Even the physical state of food (solid/liquid) influences the glycaemic response pattern, i.e.…”
Section: Introductionmentioning
confidence: 99%